Implementation of Service Marketing Strategies to Improve Donor Experience and Loyalty on The Infak.Id Platform - Rendi Septiyan Nugraha; Nila Armelia Windasari (PT Mattawang Mediatama Solution, 2024)
This research aims to explore the factors that cause the number of users who donate again on the Infak.id platform to be quite low and experience stagnant growth and help map business improvisations that can be made to overcome these business issues. By using a quantitative approach and Canva persona tools, customer journey, and service marketing design, the results show that infak.id donors have a less interesting experience when entering the final phase in the process of interacting with the infak.id platform, so it is necessary to develop business process flows and new features to increase user interest in the infak.id platform and ultimately have an impact on improving infak.id's financial performance, especially those from old donors who donate again